Beyond Subordination: Stigmatisation, Intersection, and Coping Strategies of Women with Niqab in Langsa, Aceh. - Siregar, Mawardi; Fitria, Syiva; Sembiring, Masdalifah; Zulkifli, Zulkifli (Pertanika Journal of Social Sciences & Humanities, 2026)
Studies on the practice of wearing the niqab or niqab as a living culture of Muslim women have focussed primarily on transnational political contexts and the association with radical religious movements. Many studies have been conducted on Muslim minority communities, while scholars have neglected the subjective experience of women with the niqab in Muslim-majority microenvironments. Based on a case study of a small Indonesian city that practices Islamic law, this article examines stigmatisation, environmental intersectionality, and the coping strategies of niqab-wearing women to overcome unequal power relations. The current study used an ethnographic approach, implementing observation, interviews, and Focus Group Discussions (FGD) as data collection techniques. Using scientific interdisciplinary theory, the main findings of this study reveal that women with a niqab are not passive subjects. Still, they are active agents in overcoming every element that might create stigma. A creative coping strategy is chosen by women with niqabs as an attempt to overcome the stigma pointed at them so that they can subsist and be productive, without any connections with radical actions. In addition, this creativity demonstrates women with a niqab's ability to overcome subordination to others.